Negara Hukum yang Bersifat Demokratis: Konsep dan Implementasinya - WIWIN YULIANINGSIH (Jurnal Hukum Lex Generalis, 2025)
The state of law is a fundamental concept in modern government systems that emphasizes the supremacy of law in regulating the life of society and the state. In a state of law, government power is limited by law to ensure justice, human rights, and legal certainty for all citizens. A democratic rule of law is a form of government in which the law not only binds every individual and institution, but also ensures the existence of democratic principles that respect human rights, equality, and people's participation in the decision-making process. This article discusses the definition of a democratic rule of law, its main principles, and the challenges faced in its implementation.